2013
DOI: 10.1177/1941738113487165
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Injury Among Male and Female Intercollegiate Rugby Players

Abstract: R ugby has been played around the world since the late 1800s. In the United States, it was played at the collegiate level from the late 1800s through the early 1900s. However, a drastic decline in participation occurred in the United States with the rise of American football and the removal of rugby from the Olympics after the 1924 games. In the 1970s there was renewed interest, and the game has grown dramatically at both the high school and collegiate levels. Most notably, the women's game has grown at a quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 42 publications
2
63
0
1
Order By: Relevance
“…A peak for dislocations was observed in the twenties; whereas, the incidence was similar from the teens until 60 years of age for sprains. These observations support the findings of other studies describing a majority of young men in sports with ACJ injuries [23,24,27,28]. Men with acute Rockwood types III-VI do also have more associated articular lesions [33].…”
Section: Discussionsupporting
confidence: 90%
“…A peak for dislocations was observed in the twenties; whereas, the incidence was similar from the teens until 60 years of age for sprains. These observations support the findings of other studies describing a majority of young men in sports with ACJ injuries [23,24,27,28]. Men with acute Rockwood types III-VI do also have more associated articular lesions [33].…”
Section: Discussionsupporting
confidence: 90%
“…The reason for the male majority is their participation in occupational and leisure activities which puts them at certain higher risk than their female counterpart. 19 In the present study it was observed that 4% of the victims belonged to the age group <1 year , 12 % of the victims belonged to the age group 1-20 years, 18 % belonged to the age group 41-60 years, 28 % belonged to the age group of 61-80 years and 6% belonged to age group of >80 years. This is in accord with previous studies performed in Northern Manhattan, France, and Olmsted Country, all of which found low incidence rates of TBI in those younger than 1 year.…”
Section: Gender Distribution 1st Qtr 2nd Qtrmentioning
confidence: 79%
“…19 Increases in recent decades in athletic participation among women and recreational sport participation among both sexes have contributed to the widespread incidences of ACL injuries. 3,4 As a consequence, much has been written in the scientific literature in recent decades about the functional anatomy, surgical intervention, and physical rehabilitation of ACL injuries. Nonetheless, lesser focus has been on the causes of the injury and even less on its prevention.…”
Section: Acl Tears: Causes and Predisposing Factorsmentioning
confidence: 99%